Halal Sertification and Repeated Purchase: How is Social Accounting Implemented (Case Study at One of the Famous Cake and Bakery Shop in Indonesia) - Tantular Rachman, Yoga; Sri Wulandari, Neni (International Journal of Psychosocial Rehabilitation, 2020)
This study raises the issue of social accounting, which is a non-economic factor for companies to obtain and increase profits. One of the non-economic factors is halal certification for products related to the buyer's decision to buy the product again continuously. In Indonesia, with a large population and the majority being Muslims, paying attention to non-economic factors such as halal certification is very important. At present, amid the development of sharia in Indonesia, the halal lifestyle is a matter of great concern. Using simple regression analysis, the results of the study show that there is a significant effect of halal certification on the buyer's decision to buy the same product again in the future. This research was conducted on consumers of one of the very famous cake and bread shops in Indonesia.